2002
DOI: 10.1161/01.cir.0000014447.06099.fb
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Homocysteine Concentration, Statin Therapy, and the Risk of First Acute Coronary Events

Abstract: Background-Elevated homocysteine levels are associated with increased coronary risk, and it has been suggested that homocysteine screening may provide a method to identify high-risk patients for aggressive primary prevention. Methods and Results-Homocysteine was measured at baseline and after 1 year among 5569 participants in the Air Force/Texas Coronary Atherosclerosis Prevention Study (AFCAPS/TexCAPS), a randomized trial of lovastatin in the primary prevention of acute coronary events. The effects of homocys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(10 citation statements)
references
References 20 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…Homocysteine is thought to be an early marker of future CAD risk [29]. In our study, male subjects had higher homocysteine concentrations than female subjects.…”
Section: Discussionmentioning
confidence: 45%
“…Homocysteine is thought to be an early marker of future CAD risk [29]. In our study, male subjects had higher homocysteine concentrations than female subjects.…”
Section: Discussionmentioning
confidence: 45%
“…The findings of community studies and studies among healthy persons differ with regard to CHD risk and increased levels of tHcy, with some reporting a positive association [2, 4,6,7,8,9, 22, 23] but not most [10,11,12,13,14,15,16,17, 24, 25]. The summary of odds ratios of CHD associated with tHcy concentration have usually been lower in prospective than in retrospective case-control studies [26].…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional and case-control studies have mainly reported an increased prevalence of coronary heart disease (CHD) with increasing levels of serum total homocysteine (tHcy) [2,3,4]. However, some prospective studies (mostly nested case-control studies) have found tHcy to be an independent predictor of incident CHD [5,6,7,8,9], whereas others have not [10,11,12,13,14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…This reduction was associated with a decrease in the risk of cardiovascular events. In the AFCAPS/ Texcaps (Air Force/Texas Coronary Atherosclerosis Prevention) study, subjects with a total cholesterol level below the median but an hs-CRP greater than the median had a reduced risk with lovastatin treatment [35]. Subjects with an hs-CRP below the median did not have such a benefit.…”
Section: Effect Of Treatment Strategies On Hs-crp Levelsmentioning
confidence: 99%